Gun victimization in the line of duty - Nix, Justin (Criminology & public policy, 2020)
Research Using open-source data from the Gun Violence Archive (GVA), we analyze national- and state-level trends in fatal and nonfatal firearm assaults of U.S. police officers from 2014 to 2019 (N = 1,467). Results show that (a) most firearm assaults are nonfatal, (b) there is no compelling evidence that the national rate of firearm assault on police has substantially increased during the last 6 years, and (c) there is substantial state-level variation in rates of firearm assault on police officers. Policy Implications GVA has decided strengths relative to existing data sources on police victimization and danger in policing. We consider the promises and pitfalls of this and other open-source data sets in policing research and recommend that recent state-level improvements in use-of-force data collection be replicated and expanded to include data on violence against police.